Click beetle larvae from Cretaceous Burmese amber represent an ancient Gondwanan lineage - Robin Kundrata; Simone Policena Rosa; Katerina Triskova; Gabriela Packova; Johana Hoffmannova; Jan Brus (Scientific Reports)
Abstract The click beetles (Elateridae) represent the major and well-known group of the polyphagan superfamily Elateroidea. Despite a relatively rich fossil record of Mesozoic Elateridae, only a few species are described from the Upper Cretaceous Burmese amber. Although Elateridae spend most of their lives as larvae, our knowledge on immature stages of this family is limited, which is especially valid for the fossils. So far, only a single larval click beetle has been reported from Burmese amber. Here, we describe two larval specimens from the same deposit which based on their morphology unambiguously belong to the predominantly Southern Hemisphere subfamily Pityobiinae, being the most similar to the representatives of tribe Tibionemini. However, since the larvae of the closely related bioluminescent Campyloxenini have not yet been described, we place our specimens to Tibionemini only tentatively. One species of Pityobiinae was recently described from Burmese amber based on adults, and we discuss if it can be congeneric with the here-reported larvae. Recent representatives of the Tibionemini + Campyloxenini clade are known from South America and New Zealand, and this group is hypothesized to have a Gondwanan origin. Hence, the newly discovered Burmese amber larvae may further contribute to a recently highly debated hypothesis that biota of the resin-producing forest on the Burma Terrane, which was probably an island drifting northward at the time of amber deposition, had at least partly Gondwanan affinities. The discovery of enigmatic click beetle larvae in the Upper Cretaceous Burmese amber sheds further light on the palaeodiversity and distribution of the relatively species-poor Gondwanan clade of click beetles, which contain a recent bioluminescent lineage, as well as on the taxonomic composition of the extinct Mesozoic ecosystem.